PENGARUH STRUKTUR KEPEMILIKAN, TAX AVOIDANCE, AUDITOR SWITCHING DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Arfiana Devi Muftiarani; Anissa Amalia Mulya (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to analyze the factors that affect the timeliness of financial statement submission. The data used are secondary data with the population of wholesale (durable & non-durable goods) service sub-sector companies listed on the Indonesia Stock Exchange. The sample used is 20 companies with observation year 2015-2018. Sampling technique used is purposive sampling with method of logistic analysis. The results of this study indicate that the tax avoidance affect the timeliness of the delivery of financial statements, while ownership structure, auditor switching and reputation of public accounting firms does not affect the timeliness of financial reporting.